2012
DOI: 10.5754/hge11781
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of BCRP Expression and Restoration of Sensitivity to Chemotherapy in Multidrug-Resistant Hepatocellular Carcinoma Cell Line HEPG2/ADM by RNA Interference

Abstract: These data indicated that pSUPER-BCRPs could modulate MDR and may present a new approach to overcome BCRP-mediated drug resistance in HEPG2/ADM cells. It may reverse multidrug resistance phenotype and therefore provide promising therapeutic modalities in the treatment of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…In this case both decrease of ABC 0 and increase of CYP levels results in lower EC 50 values, while increase of ABC 0 and decrease of CYP level results in higher EC 50 values. These results are in agreement with RNA silencing experiments, where cytotoxicity to doxorubicin increased after silencing of ABCG2 [ 22 ], whereas cytotoxicity to cyclophosphamide decreased after the silencing of CYP3A4 [ 21 ].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…In this case both decrease of ABC 0 and increase of CYP levels results in lower EC 50 values, while increase of ABC 0 and decrease of CYP level results in higher EC 50 values. These results are in agreement with RNA silencing experiments, where cytotoxicity to doxorubicin increased after silencing of ABCG2 [ 22 ], whereas cytotoxicity to cyclophosphamide decreased after the silencing of CYP3A4 [ 21 ].…”
Section: Resultssupporting
confidence: 88%
“…This opened the possibility for the calculation of in silico cytotoxicity curves resembling experimentally obtained results. Our results of in silico toxicity analysis are in agreement with RNA silencing experiments described in the literature [ 21 , 22 ].…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…BCRP transports a wide range of conjugated and unconjugated xenobiotics and was demonstrated to mediate resistance to chemotherapeutic agents like daunorubicin and mitoxantrone [ 15 , 16 ]. As far as HCC is concerned, there is evidence associating BCRP overexpression with resistance to doxorubicin in vitro [ 17 ]. It was reported that Sfb intracellular accumulation is modulated by P-gp, MRP2 and BCRP [ 18 , 19 ] due to the extrusion of either Sfb itself or its metabolites, which exhibit also chemical properties typical of P-gp and MRP2 substrates [ 10 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Specific siRNAs targeting chemoresistant genes designed using RNAi technology have shown considerable potential in reversing MDR (Maddalena et al, 2011;Li et al, 2012;Zhao et al, 2012;Yin et al, 2012). In the current study, we constructed recombinant lentivirus containing siRNA targeting GST-π and polβ genes.…”
Section: Discussionmentioning
confidence: 99%